2017
DOI: 10.1038/s41467-017-01009-1
|View full text |Cite
|
Sign up to set email alerts
|

Arginine methylation catalyzed by PRMT1 is required for B cell activation and differentiation

Abstract: Arginine methylation catalyzed by protein arginine methyltransferases (PRMT) is a common post-translational modification in mammalian cells, regulating many important functions including cell signalling, proliferation and differentiation. Here we show the role of PRMT1 in B-cell activation and differentiation. PRMT1 expression and activity in human and mouse peripheral B cells increases in response to in vitro or in vivo activation. Deletion of the Prmt1 gene in mature B cells establishes that although the fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 42 publications
6
38
0
Order By: Relevance
“…2B). The observation of B cell maturation defects is consistent with other reports using B cell specific PRMT1 KO mice [17][18][19].…”
Section: Loss Of Prmt1 Affects Terminal Hematopoietic Differentiationsupporting
confidence: 92%
See 1 more Smart Citation
“…2B). The observation of B cell maturation defects is consistent with other reports using B cell specific PRMT1 KO mice [17][18][19].…”
Section: Loss Of Prmt1 Affects Terminal Hematopoietic Differentiationsupporting
confidence: 92%
“…Our flow-cytometry analysis showed a significant decrease in the frequency and absolute number of mature B cells in PRMT1 f/f /Mx1-CRE mouse BM, and, consistent with other's results [17], found that mice with a B-cell-specific deletion of PRMT1 display a partial block in B cell development at the pre-B cell stage, confirming that PRMT1 is required for lymphocyte development. Infantino et al [19] undertook an immunology analysis on mice with Prmt1 deletion in mature B cells. Their analysis revealed that PRMT1-catalyzed protein substrate methylation is essential for normal B cell proliferation, differentiation and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Typhi infection. These results are in agreement with previous data showing that naïve B- and T-cells are less sensitive to perturbations of arginine methylation than memory cells 33 , 34 . Arginine methylation also controls the strength of cell signaling via γ chain (γc)-family cytokines, including interleukin-2 (IL-2), IL-4, IL-7, IL-9, IL-15, and IL-21 35 , that are essential for T-cell development and function 36 .…”
Section: Discussionsupporting
confidence: 93%
“…There is a wide variety of post‐translational modifications that can affect gene expression. While most of histone modifications are located on histone tails, epigenetic modifiers can also modify the histone core itself (eg, H3K79me2) or proteins (such as protein arginine methyltransferases). Histone modifications include: acetylation, methylation, ubiquitination, phosphorylation, SUMOylation and ADP‐ribosylation.…”
Section: Modulation Of Dna Methylation and Histone Modifications Are mentioning
confidence: 99%